Pengaruh Loan to Deposit Ratio dan Tingkat Perputaran Kas Terhadap Profitabilitas LPD Se-Kecamatan Denpasar Selatan - Ni Putu Della Widya Pramesti; Ni Wayan Alit Erlina Wati; Kadek Dewi Padnyawati (UNHI Press, 2026)
Lembaga Perkreditan Desa (LPD) or Village Credit Institutions are community-owned microfinance institutions that play a vital role in managing public funds and improving rural economic welfare. However, in practice, LPDs face challenges in efficiently managing funds and achieving profitability. This study intends to investigate the influence of Loan to Deposit Ratio and Cash Turnover Rate on Profitability in LPDs located in the South Denpasar District. The research utilizes a quantitative approach employing secondary data from annual financial reports of 11 LPDs for the period of 2021 to 2024, resulting in a total of 44 observations. Using the most recent version of SPSS, multiple linear regression is the analytical technique used. The findings show that while the Cash Turnover Rate significantly reduces profitability, the LDR has no discernible impact. These findings can provide strategic input for LPD managers in improving the efficiency of credit distribution and cash management to optimally impact the institution's financial performance.